Implementation of Risk-Based Inspection (RBI) in Condensate Separator and Storage Vessel: A Case Study - Nurhadi Siswantoro; Dwi Priyanta; Jamal Ramadhan (Institut Teknologi Sepuluh Nopember, 2021)
In the processing of oil and gas, a pressure vessel is an important piece of equipment. It needs a method to prevent the failure of the pressure vessel. The Risk-Based Inspection (RBI) is a systematic approach to the inspection management method for equipment based on the level of risk. RBI is expected to provide sufficiently accurate recommendations to prevent equipment failures. In this research, the objects to be carried out are the 10V2102 condensate separator and the 10V2103 condensate storage vessel. According to RBI analysis, the risk category of the current RBI date is low risk for the condensate separator 10V2102 and condensate storage vessel 10V2103. Meanwhile, the inspection date of Condensate Separator 10V2102 is 2 April 2026 and 11 February 2027 for Condensate Storage Vessel 10V2103 and selected inspection methods are Visual Testing, Ultrasonic Testing (UT), Radiography Test (RT), Eddy Current Test, and Magnetic Particle Inspection.